Dominica. Significant Achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Dominica during 2019 are identified, with respect to the needs and interests of the country, strengthening issues of quality, health and food safety, especially in the area of exports. Likewise, it collaborated in supporting farmers to achieve certification of their farms, in the correct handling of pesticides; as well as to strengthen the capacities of technicians in the planning and monitoring of work programs. Finally, work was done on apiculture, pest control and resilience to climate change, through the Agricultural Resilience Center and the use of climate-smart technologies.